2020
DOI: 10.3390/land9030062
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Public Complaints to Evaluate Ecosystem Services

Abstract: Reducing the demands placed on ecosystems can maximize the benefits they provide. Therefore, this study examines public complaints about the environment to analyze the pressure placed on the ecosystem spatially and temporally. Environment-related public complaints filed in the city of Namyangju were examined. The city sources its water from the Han River and is poised to implement a payment system for ecosystem services. Many complaints were filed regarding noise and oscillation, dust scattering, wildlife, air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This technique also identifies distinct characteristics of the area based on the needs of local citizens. Furthermore, combining big data (social networking service data such as Twitter, Facebook, YouTube, and Flickr) [19,20] and regional micro data (in-depth interviews and civil complaints) [21,22] would enable the prioritization of land-use policies specialized for each location. When determining such priorities, spatial text mining could provide important data that represents the needs and opinions of local residents.…”
Section: Discussionmentioning
confidence: 99%
“…This technique also identifies distinct characteristics of the area based on the needs of local citizens. Furthermore, combining big data (social networking service data such as Twitter, Facebook, YouTube, and Flickr) [19,20] and regional micro data (in-depth interviews and civil complaints) [21,22] would enable the prioritization of land-use policies specialized for each location. When determining such priorities, spatial text mining could provide important data that represents the needs and opinions of local residents.…”
Section: Discussionmentioning
confidence: 99%
“…Text mining produces quantified numbers, which can be used for mapping. This method has been defined as ‘spatial text mining’ 9 , 25 . Through a factor analysis between spaces and significant words, this technique can identify the main keywords used in each response and the characteristics of each distribution.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…In other study, Chen et al (2021) identified the affecting factors of customers satisfaction from unstructured online comments by lessening personal communication to collect these reviews. Lee and Choi (2020) studied public environmental complaints to investigate the factors that contribute to reducing ecosystem benefits. They performed statistical and spatial analyses on the complaints received by the Namyangju government.…”
Section: Related Workmentioning
confidence: 99%